Evaluation the effect of the Cartilaginous Columellar Strut Graft on Nasal Breathing Satisfaction after Septoplasty - Mohajeri, Babak; Yarmohammadi, Mohammadebrahim; Izadi, Poopak (ENT Updates, 2024)
Background: Septoplasty is one of the most common operations in adults in order to improve qualitative and quantitative scores in nasal obstruction. Using Columellar strut graft in septoplasty is not a routine technique but helps not only to correct septal deviation but also provides a better breathing status. The aim of this study was to compare the outcome of routine septoplasty with septoplasty with Columellar strut graft in nasal breathing satisfaction. Methods: Forty patients with deviated nasal septum who scheduled for septoplasty, were randomly assigned into 2 equal groups. In first group routine septoplasty and in second group septoplasty with columellar strut graft were performed. Visual Analog Scale (VAS) was used to evaluate nasal breathing satisfaction, and Nasal Obstruction Symptom Evaluation (NOSE) score was used for the assessment of nasal obstruction. Results: According to VAS and NOSE score, nasal breathing satisfaction and nasal obstruction improved significantly in septoplasty with columellar strut graft group in comparison with the routine septoplasty group (P < .001). Conclusion: Using cartilaginous columellar strut graft in septoplasty is effective in improving nasal breathing satisfaction in patients after septoplasty. Therefore it should be recommended in septoplasties.